Penerapan Prinsip Kehati-Hatian Dalam Menetapkan Jaminan Pada Perjanjian Kredit di PT Bank Negara Indonesia (Persero) TBK. Cabang Rengat - Abdullah, Fikri; Firdaus, Firdaus; Hendra, Rahmad (Jurnal Ilmiah Wahana Pendidikan, 2024)
The precautionary principle is one of the principles in bank business activities in Indonesia which must be implemented and implemented by banks. This prudential nature requires banks to always be alert and careful in carrying out their business, that is, they must always be consistent and obedient in implementing statutory regulations in the banking sector based on professionalism and good faith. The aim of this research is to find out how the precautionary principle is implemented in credit agreements at PT. Bank Negara Indonesia Tbk. Rengat Branch and to find out what PT. Bank Negara Indonesia Tbk. Rengat Branch to apply the principle of prudence in determining credit agreements. The type of research that the author uses is sociological legal research, namely research to find the truth which begins with the process of collecting data or facts that occur in the field, using basic concepts known from sociology as a science. Sociological research was conducted to identify efforts and implementation of the precautionary principle in credit agreements at PT Bank Negara Indonesia Tbk. Rengat Branch. From the results of the research the author found that the application of the precautionary principle in determining collateral in credit agreements at PT. Bank Negara Indonesia Tbk. The Rengat branch is still not doing well, this can be proven by the large number of debtors who have problem loans at PT. Bank Negara Indonesia Tbk. Rengat Branch so that the debtor's guarantee was auctioned at a price that dropped drastically, because the debtor's guarantee suffered a lot of damage and PT. Bank Negara Indonesia Tbk. It is also difficult for the Rengat branch to find people who want to buy the guarantee. It can be concluded that the implementation of the precautionary principle has not been implemented and the efforts of PT. Bank Negara Indonesia Tbk. In determining collateral, the Rengat Branch must apply the principle of prudence and must pay attention to the requirements which are often called "the 5 C's analysis of credit", namely collateral or guarantees.